Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper evaluates Hungary's growth and current account performance by using a simple empirical model that provides benchmarks to measure GDP growth rates and current account deficits. The cross-country analysis suggests that in general, larger current account deficits are associated with faster income convergence. The model's benchmark for Hungary suggests that its current account deficit has been larger than would be expected based on the income convergence process. The paper describes the motivation for, and specifics of, the modeling strategy, and the data used in the analysis.